COMPASSION FATIGUE, BURNOUT AND COMPASSION SATISFACTION AMONG NURSES WORKING IN A TERTIARY CARE HOSPITAL OF NEPAL DURING COVID-19 PANDEMIC - Poudyal, Sunita; Sharma, Kalpana; Ghimire, Srijana (Journal of Chitwan Medical College, 2022)
Background: Nurses frequently experience compassion fatigue and burnout, which have an impact on both their personal lives and patient care. The aim of this study was to assess compassion fatigue, burnout and compassion satisfaction among nurses working in a tertiary care hospital of Nepal during COVID-19 Pandemic.Methods: A cross-sectional study was conducted among 230 nurses working in Chitwan Medical College Teaching Hospital. Simple random sampling technique was used to select the study sample. Data were collected using self-administered questionnaire with Professional Quality of Life Questionnaire (ProQOL) from 15th July 2021AD to 15th September 2021AD. Data were analyzed in SPSS version 15 for window using descriptive and inferential statistics.Results: Majority of the nurses reported moderate level of compassion fatigue 177 (77.0%), burnout 176 (76.5%) and compassion satisfaction 164 (71.3%) whereas only 65 (28.3%), 8 (3.5%) and 2 (0.9%) nurses had high level of compassion satisfaction, fatigue and burnout respectively. Level of compassion fatigue and burnout were significantly associated with professional protection training. There was significant relationship found among components of ProQOL where compassion satisfaction was negatively correlated with fatigue (r= -.149: p-0.024) and burnout (r=-.487: p-0.000) but compassion fatigue and burnout were positively correlated with each other (r=0.522, p=